2013
DOI: 10.1111/pai.12120
|View full text |Cite
|
Sign up to set email alerts
|

Oral treatment with β‐lactoglobulin peptides prevents clinical symptoms in a mouse model for cow's milk allergy

Abstract: Prior exposure to specific peptides of β-lactoglobulin reduces the allergic response to whey, which may involve regulatory dendritic and T cells. Combining peptides with a sGOS/lcFOS/pAOS-containing diet enhances this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 37 publications
8
65
1
Order By: Relevance
“…Interestingly, despite the absence of clinical symptoms, we found a significantly increased whey-specific IgE response in whey hydrolysate sensitized animals. This also corroborates the findings of other groups showing no clinical symptoms despite a high specific IgE response in sensitized mice [35][36][37]. It should be noted that variability between individual mice in the whey hydrolysate group was high.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, despite the absence of clinical symptoms, we found a significantly increased whey-specific IgE response in whey hydrolysate sensitized animals. This also corroborates the findings of other groups showing no clinical symptoms despite a high specific IgE response in sensitized mice [35][36][37]. It should be noted that variability between individual mice in the whey hydrolysate group was high.…”
Section: Discussionsupporting
confidence: 90%
“…immunisation suggests the exclusion of tolerance mediated by IgG [19]. Rather, the mechanism may involve generating BLG-specific regulatory T cells, as suggested by a previous study using preventive administration of specific peptides derived from BLG [20]. …”
Section: Discussionmentioning
confidence: 99%
“…There are many studies aiming to reduce the allergenicity of β-LG by using enzymatic hydrolysis [2, 3] or chemical modification techniques [4, 5]. In addition, many researchers have focused on β-LG with regard to oral tolerance induction [6-9]. However, in clinical practice, it is reported that casein, rather than β-LG, is the more dominant causal allergen in CMA [10, 11].…”
Section: Introductionmentioning
confidence: 99%